THE IMPACT OF AN ADDITIONAL NURSE ASSISTANT DURING EVENING SHIFTS ON NURSES’ PERCEPTIONS OF JOB DEMANDS, JOB RESOURCES AND WELL‐BEING - Nadyah Sulaiman Lahelm Alanazi, Saeedah Alwan Jalawi Aldhafeeri, Faiz Fahad Manea Aldhafeeri, Hanan Sulaiman Alohaylim Alanazi, Suad Alwan Jalawi Aldhafeeri, Salem Alhumaidi Salman Aljameeli (Chelonian Research Foundation, 2022)
Aim: Nurses' well-being is often compromised due to high workloads and job demands, especially during evening shifts when resources are limited. This study aims to investigate the effects of integrating a nurse assistant into ward staffing during evening shifts on nurses' perceptions of job demands, job resources, and well-being. Design: This study employs a pre-post pilot design to compare nurses' perceptions before and after the addition of a nurse assistant to ward staffing during evening shifts, focusing on job demands, job resources, and well-being. Methods: Twenty-eight nurses from a top clinical hospital participated in this study, completing baseline and follow-up surveys using validated measures for job demands (workload and physical demands), job resources (autonomy and task clarity), and well-being (recovery from work and sleep problems). Results: Following the addition of a nurse assistant, nurses reported reduced job demands, including lower workloads and fewer physical demands, as well as fewer sleep problems compared to baseline. However, no significant changes were observed in job resources such as autonomy and task clarity, or in recovery difficulties. Conclusions: The findings suggest that integrating a nurse assistant during evening shifts can alleviate workloads, physical demands, and sleep problems among nurses. Impact: This study underscores the potential of adding a nurse assistant to nursing teams during evening shifts to address heavy job demands and sleep-related issues. Further research with larger sample sizes and control groups is recommended to better assess the intervention's effectiveness and cost-effectiveness.